BLENDED LEARNING SEBAGI SISTEM PEMBELAJARAN PADA MASA COVID-19 DI MI NW 1 KEMBANG KERANG - Husairi, Husairi (Alifbata : Jurnal Pendidikan Dasar, 2022)
The atmosphere is tense due to the Covid-19 virus outbreak. Several schools were forced to close by the government and some also entered with shortened face-to-face time. Schools that conduct face-to-face must comply with the provisions of reducing face-to-face time and using health protocols, and some are also conducting online learning. And MI NW 1 kembang scallops is a school or madrasa that carries out online and offline learning processes or commonly known as the Blendend Learning system. In this study the authors used qualitative research methods, which intended to interpret the phenomena that occurred and carried out in various ways involving various existing data collection techniques. In general, the results of this study show that the implementation of learning at MI NW 1 Kembang Clam uses the Blended Learning system, even though it is not yet running effectively. Blended learning is a policy of the head of the madrasa which is based on the results of the meeting of the madrasah and the school committee in the MI NW 1 kembang shell environment. The process of learning in shifts or alternately. Blended learning evaluation is handed over to each teacher.